Does the organization–employee relationship matter? - Pathak, Deepti (Economic and business review, 2025)
The study examines the relationship between the organization–employee relationship (OER), well-being, and work performance of remote workers who were mandated to work from home because of the uncertainties and health risks brought about by the COVID-19 pandemic. This study focuses on the work performance of the employees contributed through positive psychological well-being and positive OERs. A comprehensive nationwide survey was undertaken, involving a sample size of 1289 full-time IT employees in India, with the objective of determining the impact of well-being on individual work performance. Results from the analyses indicate that though the employees with limited experience of work from home found it challenging during the initial stages of the pandemic, the positive OERs positively and significantly affected their well-being and overall work performance by helping them overcome the stress created by the pandemic.
Keywords: delo na daljavo; delovna razmerja; delovni učinek; labour relations; telework; work performance